2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.24409
|View full text |Cite
|
Sign up to set email alerts
|

Learning Management Systems: What More can we Know?

Abstract: Learning management systems (LMS) are ubiquitous among colleges and universities worldwide, however they are thought of as a transactional warehouse rather than an opportunity to understand student learning outside of the classroom. Each LMS is used differently across campuses, and even across sections of the same courses taught by different instructors. For instance, one instructor might utilize a gradebook feature which allows students to view their assignment grades, while another instructor in the same cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
0
5
1
Order By: Relevance
“…To explore how overall student activity correlates to performance, we used Pearson's correlation test on the students' individual total activity and their final grades. Contrary to some literature [5], [10], [13], [16], we did not find a statistically significant correlation at the specified level of p < 0.05 between individual students' total activity and their final grade, as noted by the weak positive trend in Figure 6. One hypothesis for the weak correlation is that multiple factors, such as personal situations or exam time limits, affect student grades.…”
Section: Correlational Analysiscontrasting
confidence: 99%
See 3 more Smart Citations
“…To explore how overall student activity correlates to performance, we used Pearson's correlation test on the students' individual total activity and their final grades. Contrary to some literature [5], [10], [13], [16], we did not find a statistically significant correlation at the specified level of p < 0.05 between individual students' total activity and their final grade, as noted by the weak positive trend in Figure 6. One hypothesis for the weak correlation is that multiple factors, such as personal situations or exam time limits, affect student grades.…”
Section: Correlational Analysiscontrasting
confidence: 99%
“…For example, 4 PM is 4:00:00 The second phase of the analysis was determining if student activity correlated with performance in the course. Studies have found that LMS tracking variables such as specific tool use [5], [16], content interactions [13], and quantity of online sessions [10] correlate with the students' final grades. Our study used Pearson's correlation test, similar to Brozina and Knight (2015), to assess the correlation of student activity with course performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evolution of online learning has produced unprecedented amounts of student data for understanding the individual learning dynamics of online learners (Brozina and Knight 2015). One type of big data (massive sets of data computationally analyzed for patterns and trends) central to online learning is learning analytics (LA).…”
Section: Introductionmentioning
confidence: 99%